Position paper of the Group of Fifteen on the New World Order (The Group GenevaCH, 1992)
Looks briefly at the current world situation then focuses on issues such as democratization, human rights and development; disarmanent and development; eradication of poverty; terrorism and drug trafficking; foreign debt and the flow of resources; international trade; primary commodities; regional economic groupings; environment and development; population; South-South cooperation; and the role of the United Nations.
DC